2015
DOI: 10.1242/dev.114454
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal polarization

Abstract: Neurons are highly polarized cells with structurally and functionally distinct processes called axons and dendrites. This polarization underlies the directional flow of information in the central nervous system, so the establishment and maintenance of neuronal polarization is crucial for correct development and function. Great progress in our understanding of how neurons establish their polarity has been made through the use of cultured hippocampal neurons, while recent technological advances have enabled in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 65 publications
2
109
0
Order By: Relevance
“…Pyramidal neurons first extend multiple minor processes and are called multipolar (MP) cells in intermediate zone (IZ). These MP cells subsequently transform into bipolar (BP) cells with a trailing process and a leading process, which finally develop into an axon and a dendrite, respectively 2, 3 . BP cells are completely polarized and migrate toward the cortical plate (CP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyramidal neurons first extend multiple minor processes and are called multipolar (MP) cells in intermediate zone (IZ). These MP cells subsequently transform into bipolar (BP) cells with a trailing process and a leading process, which finally develop into an axon and a dendrite, respectively 2, 3 . BP cells are completely polarized and migrate toward the cortical plate (CP).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Rho-kinase phosphorylates and inactivates p190RhoGAP, thereby leading to sustained activation of RhoA 56 . Rho-kinase also inactivates Rac1 through phosphorylation of Par3 and Rac GEFs (STEF/Tiam) 1, 3, 57 . Following Rho-kinase activation by long-range inhibitory signaling, the activated RhoA may be sustained and diffused by Rho-kinase-dependent inactivation of RhoGAP, ultimately guaranteeing neuronal polarity through multiple pathways in minor neurites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization of neuron cells characterizes the formation of axons and dendrites in neuron cells and is crucial for neuronal functionality 54, 55 . Many extra – and intracellular processes are responsible for the establishment and maintenance of cell polarity, such as protein diffusion and scaffold formation, secretory pathways, and ion channel activity 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Neuronal cells, which have unique characteristics with a distinct morphology, critically require a well-regulated system of synthesis and degradation of proteins at the time of development, as well as in later life stages (Yi and Ehlers, 2007; Takano et al, 2015). They maintain a polar shape, in order to develop a functional neuronal circuitry (Tahirovic and Bradke, 2009).…”
Section: Key Questions and Future Prospectivementioning
confidence: 99%